The Wilms tumor protein Wt1 contributes to female fertility by regulating oviductal proteostasis - Nathan, Abinaya; Holschbach, Verena; Toth, Bettina (Human molecular genetics, 2017)
Although the zinc finger transcription factor Wt1 has been linked to female fertility, its precise role in this process has not yet been understood. We have sequenced the WT1 exons in a panel of patients with idiopathic infertility and have identified a missense mutation in WT1 in one patient out of eight. This mutation leads to an amino acid change within the zinc finger domain and results in reduced DNA binding.
Gesehen am 27.07.2018